2009
DOI: 10.3324/haematol.2009.013623
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution single-nucleotide polymorphism array-profiling in myeloproliferative neoplasms identifies novel genomic aberrations

Abstract: -resolution single-nucleotide polymorphism array-profiling in myeloproliferative neoplasms identifies novel genomic aberrations. Haematologica. 2010;95: 666-669. doi:10.3324/haematol.2009 This is an open-access paper. ABSTRACT © F e r r a t a S t o r t i F o u n d a t i o ngain of 1q (n=4), and trisomy 8 (n=4), followed by loss of 5q11-q13 and 13q12-q21 in single cases (Table 1). While 20q losses occurred in all MPN subgroups, gain of 9p / trisomy 9 was restricted to PV and secondary MF patients, and trisomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 13 publications
5
40
0
Order By: Relevance
“…This differs from a prior study in pediatric T-ALL and AML, where five patients show identical 1.2-Mb NF1 microdeletion, similar to the one described in neurofibromatosis [20]. However, our data are consistent with the previous studies reporting somatic heterogeneous 17q11 deletions in adult myeloid malignancies [5,6,9,21]. Interestingly, we have identified a small MDR of 0.3 Mb, which contains only four genes, NF1, and three genes embedded in intron 27b of NFI (OMG, EVI2B, and EVI2A) (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…This differs from a prior study in pediatric T-ALL and AML, where five patients show identical 1.2-Mb NF1 microdeletion, similar to the one described in neurofibromatosis [20]. However, our data are consistent with the previous studies reporting somatic heterogeneous 17q11 deletions in adult myeloid malignancies [5,6,9,21]. Interestingly, we have identified a small MDR of 0.3 Mb, which contains only four genes, NF1, and three genes embedded in intron 27b of NFI (OMG, EVI2B, and EVI2A) (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…on May 8, 2018. by guest www.bloodjournal.org From analyzed 2 patients (UPN23 and UPN30) from a previously described cohort of MPN cases (n ϭ 151). 20 The study was approved by the internal review boards of all participating institutions and informed consent was provided according to the Declaration of Helsinki. …”
mentioning
confidence: 99%
“…NF1 is a well known negative regulator of RAS, enhancing its intrinsic GTPase activ ity via the hydrolyzation of GTP to GDP. Deletions of the NF1 tumor suppressor gene have been observed in many cohorts of patients, particularly those in chronic phrase, whereas NRAS mutations seem to primarily affect patients that have transformed to AML [38].…”
Section: Mutations Targeting the Negative Regulators Of The Jak-stat mentioning
confidence: 99%
“…Recent studies have indicated that members of this pathway, such as NF1 and NRAS, are often mutated in MPNs, contributing to the myeloproliferative phenotype [37,38]. Mutations in NRAS seem to result in the consti tutive activation of the protein, thus affecting the expres sion of the JAK2 target genes.…”
Section: Mutations Targeting the Negative Regulators Of The Jak-stat mentioning
confidence: 99%